Kajian Bliblika Tentang Kebohongan Rahap Berdasarkan Yosua 2:1-14 - Kani Kani; Yeremia Hia (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Rahap is a prostitute who lives in the city of Jericho, the name "Rahab" appears the first time in the Bible, namely in the Book of Joshua, especially in chapter 2. She comes from Canaan whose life is not right before God. but Rahap and his family got salvation when he rescued and hid the two spies from Israel by deceiving the king of Jericho's envoys. while lying is an act that is not right before God because it can harm others and himself. .hsl this is the problem where many people think that it is permissible to lie as long as it is for the good even if we see in our daily lives more people commit lies than other crimes. in this study using qualitative and exege methods.The purpose of writing this article is to get answers and a correct understanding of why Rahap's lie is considered the truth and to serve as a guide so that believers don't lie anymore but instead become honest people